Analisis Financial Distress Pada Perusahaan Sektor Ritel yang Terdaftar di Bursa Efek Indonesia Periode 2020-2023 - Hadi Satria Ganefi; Lesmana, Arief Surya; Muttaqien, Dadan Darmawan (Jurnal Ranah Publik Indonesia Kontemporer (Rapik), 2024)
The development of the retail sector is influenced by many factors such as competition, government policies and technology that have an impact on consumer patterns in consuming goods or services. This will affect the company's business activities, especially in gaining profits. This will certainly have an impact on financial performance. Poor financial conditions allow companies to face financial difficulties and even lose investor trust. The purpose of this study was to determine the overall level of financial difficulties in retail sector companies during the 2020-2023 period using the Altman Z-Score Modified method to predict financial difficulties. This study uses a non-statistical quantitative method and 12 companies were used as samples using a purposive sampling technique. The results showed that out of 12 companies, one company experienced financial distress, one company was in the gray area zone and ten companies were in the healthy category.